Stay or Leave : An analysis of decision-making factors among international students in the Czech Republic - Iakovleva, Valeriia; Vltavská, Kristýna; Fischer, Jakub, 1978-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2025)
This thesis analyses decision-making factors of international student post-study stay or departure in the Czech Republic. Drawing on survey data from international degree-seeking students, provided by the Czech National Agency for International Education and Research (DZS), it uses binary logistic regression to investigate how student experience factors and demographic variables relate to this intention. Key findings indicate that the strongest predictors are the student's country of origin and their work intensity during studies. High academic satisfaction, positive social integration, and satisfaction with pre-arrival bureaucratic procedures also emerged as significant factors positively associated with the intention to stay. The thesis has implications for Czech higher education institutions and policymakers in developing conditions for the post-study stay of international graduates, benefiting both the graduates and the host nation.
Vedoucí práce: Kristýna Vltavská
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2026
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2026
Způsob přístupu: Internet
Keywords: datové analýzy a modelování [obor bakal. práce]; bakalářské práce; bachelor's theses